IMPLICATIONSUSING ELECTRONIC STAMP DUTY AUTHENTIC AS PROOF OF ELECTRONIC DOCUMENTS IN INDONESIA - Febia Salwa Pandora; Edmon Makarim (Cepalo)
The rapid societal evolution in the digital age necessitates adaptive governmental regulations, including those governing stamp duty. The introduction of e-Materai by Finance Minister Sri Mulyani in 2020 has prompted inquiries into its efficacy as a tool for verifying document authenticity. This research aims to elucidate the utility of e-stamps in authenticating documents and to assess their societal benefits. Employing a normative approach, this research examines relevant regulations, synchronizes existing data with legal frameworks, and evaluates the implementation of stamp duty in Indonesia. Despite its historical origins in Dutch colonialism, the stamp duty system persists, albeit with deficiencies in document authentication. The lack of purchaser information and document specifics hinders the optimal function of authenticity verification. Consequently, improvements in both the stamp duty system and broader legal frameworks, particularly regarding information security, are warranted.